2018
DOI: 10.1080/10520295.2017.1406615
|View full text |Cite
|
Sign up to set email alerts
|

Caralluma fimbriataand metformin protection of rat pancreas from high fat diet induced oxidative stress

Abstract: A high fat diet promotes oxidative stress, which contributes to the development of pancreatic fibrosis. We compared the protective effects of a hydroalcoholic extract of Caralluma fimbriata (CFE) to metformin (Met) in the pancreas of Wistar rats fed a high fat diet. The experimental animals were divided into five groups: control (C), treated with CFE (C + CFE), treated with high fat diet (HFD), high fat diet treated with CFE (HFD + CFE), and high fat diet treated with metformin (Met) (HFD + Met). CFE was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Oxidative stress could have deleterious impacts on various organs and systems throughout the body, such as the heart, kidney, liver and pancreas [ 26 , 34 , 35 ]. Apart from that, the GI tract is also where oxidative stress usually emerges, which is closely associated with alterations of the gut microbiota as well as diet [ 13 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress could have deleterious impacts on various organs and systems throughout the body, such as the heart, kidney, liver and pancreas [ 26 , 34 , 35 ]. Apart from that, the GI tract is also where oxidative stress usually emerges, which is closely associated with alterations of the gut microbiota as well as diet [ 13 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…On the contrary, fat and salt usually contribute to negative effects on gut microbiota. It has been extensively reported that the high-fat diet can promote oxidative stress and therefore cause organ damage [ 35 , 38 ]. With regard to the GI tract, the alteration of dietary fat intake (from low to high) in mice was able to shift the structure and gene expression of their gut microbiota within one day [ 39 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The CFE therapy reduced acinar cell degeneration, necrosis, edema, and bleeding. Moreover, CFE proved an adjuvant therapy in the prevention or managing pancreatic damage caused by HFD [ 89 ]. Another study was conducted to check the effect of CFE (200 mg/kg body weight) and metformin (20 mg/kg body weight) on HFD-induced changes in lipid metabolism of Wister rats.…”
Section: Therapeutical Potential Of C Fimbriata Ag...mentioning
confidence: 99%
“…has shown that most of these plant species could be possible sources of new active compounds. In addition to other metabolites such as flavonoid glycosides, pregnane glycosides were reported to be the most characteristic constituents of this genus. Several recent studies highlight their importance as medicinal plants to fight against particular diabetes, obesity, gastrointestinal problems, and cancer. For instance, the raw fresh young pieces of Caralluma hexagona (Syn; Monolluma hexagona, Caralluma shadhbana) are eaten as a cure for diabetes, abdominal pain, and stomach ulcers in traditional medicines in Yemen and Saudi Arabia. , …”
Section: Introductionmentioning
confidence: 99%